Biodiversity of caridean shrimps on rocky bottoms of two preserved islands on the southeastern Brazilian coast. Issue 8 (20th October 2020) - Moraes, Isabela R. R.; Almeida, Alexandre Oliveira; Cobo, Valter José; Alves, Douglas Fernandes Rodrigues; Davanso, Thiago Maia; Castilho, Antonio Leão
ABSTRACT: This study aimed to investigate the biodiversity of caridean shrimps inhabiting the consolidated sublittoral of two Brazilian biodiversity locals Laje de Santos and Vitória Island. We provide data about species composition, cumulative species curves and ecological indexes. Additionally, we compared different sampling techniques used for cryptic fauna studies. The samples were carried out quarterly for one year, using Artificial Refuge Substrate (ASR) for the passive capture and SCUBA diving for active capture. A total of 323 individuals were sampled with 17 species recorded, 13 in Vitória Island and 12 in Laje de Santos . Alpheus formosus and Cuapetes americanus were dominant in both areas and recognized as key-species for the community. Using two-sampling methods is highly recommended for future studies due to the fact that small and translucent species were obtained with ARS and large and colourful specimens were collected during SCUBA diving expeditions. An alien shrimp from the genus Athanas was registered for the first time in a protected area in Brazil. Additionally, all these results/data are important for future management and work plans in Brazilian protected areas since decapod crustaceans are an extremely important fauna group in any subtidal ecosystem.